LIPOSSOMAS DE FOSFATIDILSERINA: POTENCIAL INTERVENÇÃO FARMACOLÓGICA NA INFLAMAÇÃO E PERDA ÓSSEA ALVEOLAR INDUZIDA POR LIGADURA EM RATOS - Campos, Letícia Antonelo (2014)
The biofilm accumulation in the subgingival region produces an inflammatory process that can lead to alveolar bone resorption and periodontal attached loss through due inflammatory mediators that induce the production and activation of enzymes and periodontal degradation tissues. Phosphatidylserine liposomes can mimic apoptotic cells effects and may modulate the host inflammatory response. This present study evaluated the effect of phosphatidylserine liposomes on the inflammatory response and alveolar bone loss ligatureinduced in rats. We used a phosphatidylserine liposome solution preparation in order to evaluate the cytotoxicity in lineage osteoblastic cells. The antiinflammatory effect was evaluated by mouse ear edema (topical application) and rat paw edema (systemic application) methods. Then, we evaluated the phosphatidylserine liposome action on gingival inflammatory response and alveolar bone loss ligature-induced in rats. The results showed phosphatidylserine liposome 50 and 250 μM concentrations were safer considering cell viability and proliferation. The phosphatidylserine liposome gel (topical application) had no anti-inflammatory action on mouse ear edema model and alveolar bone loss ligature-induced in rats. The phosphatidylserine liposome solution (systemic application) has anti-inflammatory action on rat paw edema. Although, we did not observe an effect on alveolar bone loss ligatureinduced. We conclude phosphatidylserine liposome gel and solution are easy to prepare and they have low cost. Phosphatidylserine liposoma solution (systemic application) have antiinflammatory effect on rat paw edema model. On the other hand, it have no effect on alveolar bone loss ligature-induced in rat.